Levels of Heavy Metal Lead (Pb) Aquatic Plants and Water as an Indicator of Water Quality in Brangkal Mojokerto River - Syafriliansah, M Wierdan; Purnomo, Tarzan (LenteraBio : Berkala Ilmiah Biologi, 2022)
The increase of residential and industrial areas along the drainage basin (DAS) of the Brangkal River has triggered the increase of pollution, one of which was the heavy metal lead (Pb). This study aimed to determine the level of water pollution in the Brangkal River, Mojokerto based on the levels of heavy metals (Pb) in some aquatic plants (Typha angustiolia, Ipomea aquatic, and Eichhornia crassipes) as bioindicator of water pollution. Data were taken at 3 stations with a distance between each station is ± 1000 m. The research was conducted in the dry season. The measured parameters were Pb in plants and river water’s charateristics such as temperature, pH, DO, turbidity, and current velocity. The analysis of Lead (Pb) levels was carried out at the Nutrition Laboratory, Faculty of Public Health, Airlangga University using the Atomic Absorption Spectrophotometer (AAS) method. DO and turbidity measurement were carried out at the Ecology Laboratory of the department of Biologi, Faculty of Mathematics and Natural Science, Unesa. While measuring temperature, pH, turbidity, and current velocity were carried out in situ. The results of measurement of lead (Pb) levels in aquatic plants were compared to the quality standards according to SNI 7387: 2009, while the assessment of Pb metal content and river water quality based on quality standards in PP. Nomer 82 of 2001. The results showed that the average levels of lead (Pb) at stations I, II, and III in T. angustifolia plants were (0.071, 0.085, and 0.074) ppm; I. aquatica (0.018, 0.024, and 0.017) ppm; and E. crassipes (0.073, 0.067, and 0.081) ppm. Heavy metal (Pb) levels in Brangkal River water at the station I 0.002 ppm, station II 0.002 ppm, and station III 0.006 ppm met the quality standards according to PP Nomer 82 / 2001 which was categorized good.